Caracterização das internações em uma unidade de terapia intensiva pediátrica - HUSM/RS - Benetti, Marilian Bastiani (2015)
The objective of this study is to characterize the hospitalizations that occurred in the Pediatric Intensive Care Unit (PICU) at Santa Maria University Hospital from 2006 to 2013. It is a retrospective, descriptive and cross-sectional study that evaluated 1805 patients admitted to the PICU by secondary data collection and a database built based on the Inpatient Unit Records Book.The variables considered were: sex, age, origin, cause and outcome hospitalization and length of stay. It was performed a descriptive analysis followed by non-parametric inferential analysis with a 5% significance level. Out of the 1805 patients who were hospitalized during the eight-year study (2006-2013), 56.1% were male, where 42.4% were from the city of Santa Maria and 57.6% from others cities belonging the region that HUSM is the reference (4th Health Regional Coordination) or from other locations inside Rio Grande do Sul. There was no significant difference in the number of hospitalizations related to the months or the year. The average length of stay in the PICU was 7.5 days. Most patients (41.6%) were under one old, being the most frequent age of two months. The total mortality rate was 14.3% and 85.7% of the patients discharged from the unit. There was no significant difference between mortality rate and the evaluated year (minimum of 11% in 2012 and maximum of 17.7% in 2009) and age group. The most frequent causes of hospitalization were pneumonia, abdominal postoperative, trauma and sepsis wherein mortality for sepsis was significantly higher than mortality for abdominal postoperative and trauma, but there was no difference from the mortality caused by pneumonia. The data obtained is very similar to the data from others Brazilian PICU. The knowledge of epidemiological profile of patients at PICU of HUSM, still unpublished, can contribute to the decision-making and improve the quality of the care provided to users. In addition, the use of such data through appropriate analysis, dissemination and development of protocols and practices for the team, can also contribute to subsidy future studies, as well as provide guidance for patient care.